La0.14V2O5/Reduced Graphene Oxide Composite for Aqueous Zinc−Ion Batteries with Long Cycle Life. Issue 8 (19th August 2021) - Wu, Tzu-Ho; Chen, Jheng-An; Lin, Wei-Sheng; Liang, Wei-Yuan
Abstract : Rechargeable aqueous zinc−ion batteries (ZIBs) with cost−effective and environmentally friendly characteristics show great potential for large−scale energy storage systems. Among all cathode material candidates, layered vanadates are promising owing to their suitable open structure for accommodating Zn 2+ /H + . However, the unsatisfactory rate capability and cycling stability of vanadate cathodes have hindered the practical application. Thus, the exploration of high−performance and structural stable cathode materials is urgently needed. In this study, a La0.14 V2 O5 /reduced graphene oxide composite material (denoted as LaVO/rGO) can be successfully synthesized by a facile hydrothermal procedure. With the pillar La 3+ ions and highly conductive rGO, the layered LaVO/rGO has the merits of large interlayer distance (14.7 Å), low charge transfer resistance, and high diffusion coefficient that guarantee fast kinetics of Zn 2+ /H + intercalation/de−intercalation. As a result, the LaVO/rGO cathode delivers a high−rate performance which obtains high capacity of 298 mAh g −1 at 0.3 A g −1 . Even up to 8 A g −1, high capacity of 166 mAh g −1 can be achieved. Stable cycle performance with the capacity retention of 88% over 6000 cycles is attained, benefiting from fast and reversible Zn 2+ /H + storage in the host material.